A new laboratory technique for determining the compressional wave properties of marine sediments at sonic frequencies and in situ pressures1. (29th October 2013) - McCann, Clive; Sothcott, Jeremy; Best, Angus I.
ABSTRACT: We describe a new laboratory technique for measuring the compressional wave velocity and attenuation of jacketed samples of unconsolidated marine sediments within the acoustic (sonic) frequency range 1–10 kHz and at elevated differential (confining – pore) pressures up to 2.413 MPa (350 psi). The method is particularly well suited to attenuation studies because the large sample length (up to 0.6 m long, diameter 0.069 m) is equivalent to about one wavelength, thus giving representative bulk values for heterogeneous samples. Placing a sediment sample in a water‐filled, thick‐walled, stainless steel Pulse Tube causes the spectrum of a broadband acoustic pulse to be modified into a decaying series of maxima and minima, from which the Stoneley and compressional wave, velocity and attenuation of the sample can be determined. Experiments show that PVC and copper jackets have a negligible effect on the measured values of sediment velocity and attenuation, which are accurate to better than ± 1.5% for velocity and up to ± 5% for attenuation. Pulse Tube velocity and attenuation values for sand and silty‐clay samples agree well with published data for similar sediments, adjusted for pressure, temperature, salinity and frequency using standard equations. Attenuation in sand decreases with pressure to small values below Q −1  = 0.01 (Q greater than 100) for differential pressures over 1.5 MPa, equivalent to sub‐seafloor depths of about 150 m. By contrast, attenuation in silty clay shows little pressure dependence and intermediate Q −1 values between 0.0206–0.0235 (Q = 49–43). The attenuation results fill a notable gap in the grain size range of published data sets. Overall, we show that the Pulse Tube method gives reliable acoustic velocity and attenuation results for typical marine sediments.